2020
DOI: 10.1155/2020/8642135
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide and β-Synuclein Are Involved and Interlinked in the Aging Glaucomatous Retina

Abstract: Purpose. Glaucoma, one of the leading causes of irreversible blindness worldwide, is a group of disorders characterized by progressive retinal ganglion cell (RGC) loss. Synucleins, a family of small proteins, have been of interest in studies of neurodegeneration and CNS. However, their roles and functions in glaucoma are still not completely understood and remain to be explored. Our previous studies showed that α-synuclein and H2S play a pivotal role in glaucoma. This study aims to (1) elucidate the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…68,69 β-Synuclein and γ-synuclein are expressed in retinal neurons and have been associated with glaucoma-related neurodegeneration. 70,71 To date, no convincing hypothesis has been proposed for the roles of β-synuclein in neurons, but it may act as a general synaptic chaperone. 72 In adrenal chromaffin cells, it regulates vesicle dynamics and secretory rate with mechanisms similar to those occurring in neurons.…”
Section: Distribution and Structural Features Of Synucleinsmentioning
confidence: 99%
“…68,69 β-Synuclein and γ-synuclein are expressed in retinal neurons and have been associated with glaucoma-related neurodegeneration. 70,71 To date, no convincing hypothesis has been proposed for the roles of β-synuclein in neurons, but it may act as a general synaptic chaperone. 72 In adrenal chromaffin cells, it regulates vesicle dynamics and secretory rate with mechanisms similar to those occurring in neurons.…”
Section: Distribution and Structural Features Of Synucleinsmentioning
confidence: 99%
“…H 2 S has been reported to have diverse physiologic functions, such as vasodilatation, lowering blood pressure, anti-inflammation, anti-cancer, and reducing oxidative stress [ 11 , 13 ]. Moreover, H 2 S is produced in retinal tissue and attenuates high glucose-induced human retinal pigment epithelial cell inflammation by inhibiting ROS formation [ 12 ], but some studies also illustrate H 2 S-caused retinopathy [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that administration of GYY4137, a slow-release H 2 S donor, significantly improved RGC survival under different glaucomatous injuries in vitro and in vivo [ 21 ]. The neuroprotective effect of H 2 S in the retina was partly attributed to its capability of vasorelaxation, anti-oxidative stress, neuroendocrine regulation and inflammation suppression [ 25 ] but the underlying mechanism and the specific protein interaction networks and the mechanisms involved in protective properties of H 2 S remain to be elucidated. Building on previous results, we employed a mass spectrometry-based proteomics approach to analyze the retinal proteome, and bio-informatics to algorithmically generate protein connections, which allowed us to identify the most plausible signaling pathway alterations related to H 2 S’s neuroprotective properties against ischemia-reperfusion injury in present study.…”
Section: Discussionmentioning
confidence: 99%